Exploring Apologizing Strategies in the Movie “Captain Marvel” - Erma Ainun Maghfiroh; Koesoemo Ratih (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2023)
The study explored apologizing strategies within the movie "Captain Marvel" through the analysis of illocutionary speech acts. The research adopted a qualitative approach and utilized the framework of apologizing strategies developed by Kramer-Moore and Moore. The primary data sources were the movie and its script, with instances of apologizing transcribed verbatim, along with nonverbal cues. The analysis revealed two main types of apologies: expressive and directive. Expressive apologies, demonstrated by characters like Maria, Carol, and Coulson, conveyed genuine remorse and empathy to maintain harmonious interactions. On the other hand, Talos utilized directive apologies, combining sincerity with a plea for understanding and forgiveness. These findings contribute to a deeper understanding of communication dynamics within cinematic narratives and real-world interactions. Future research could explore cultural variations in apology strategies within different genres and the impact of cultural nuances on apology portrayal in films. Overall, this study provides valuable insights into the portrayal of apologizing strategies in the movie "Captain Marvel" and how they contribute to the dynamics of communication and character development. The identification of expressive and directive apology types showcases the complexity of human interactions and emotions within the context of a popular cinematic narrative.